Development of Basic Physics Teaching Materials Based on Science, Technology, Engineering, and Mathematics (STEM) In Industrial Engineering Study to Improve Student's Life Skill - Diana Ayu Rostikawati; Dedy Khaerudin; Asep Saefullah (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2022)
The purpose of this study was to develop Basic Physics teaching materials based on STEM, measure the feasibility of Basic Physics teaching materials based on STEM from the aspect of validity and practicality and measure the effectiveness of Basic Physics teaching materials based on STEM in improving Life Skills through student responses. This study used ADDIE model, which consists of 5 (five) steps, e.g Analysis, Design, Development, Implementation, and Evaluation. Produced a teaching material based on Science, Technology, Engineering, And Mathematics (STEM) on Dynamic Electricity concept. The developed teaching materials consist of seven materials, e.g Electric Current, Electrical Measuring Instruments, Ohm's Law, Resistance of a Conductor, Circuit Resistance, Kirchoff's Law, and Dynamic Electrical Applications. Teaching materials are also equipped with practice questions, practical instructions, project worksheets and additional reading lists. The results of the validation show that the teaching materials are feasible and meet the requirements to be used in the learning process of Basic Physics. The results of the implementation of teaching materials indicate that teaching materials have an influence and can improve student life skills. The results of responses to the quality of teaching materials showed that most students gave positive responses to teaching materials and stated that Basic Physics teaching materials based on STEM for Dynamic Electricity concept had been understood and met student learning expectations.Keywords: Teaching Material, STEM, Life Skill